Znaczenie międzynarodowego stowarzyszenia controllerów dla budowy prestiżu zawodu controllera - Jaworska, Elżbieta (Significance of International Association of Controllers For Structure of the Prestige of Controller Profession, 2008)
In the article is indicated the role of the controller in the enterprise as well as the International Association of Controllers, which advances and supports the controller activities on the world.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 24-30